Inferring biallelism of two FSH receptor mutations associated with spontaneous ovarian hyperstimulation syndrome by evaluating FSH, LH and HCG cross-activity. Issue 5 (May 2019) - Lazzaretti, Clara; Riccetti, Laura; Sperduti, Samantha; Anzivino, Claudia; Brigante, Giulia; De Pascali, Francesco; Potì, Francesco; Rovei, Valentina; Restagno, Gabriella; Mari, Caterina; Lussiana, Cristina; Benedetto, Chiara; et al.
Abstract: Research question: What is the cumulative effect of two follicle-stimulating hormone receptor (FSHR) mutations in spontaneous ovarian hyperstimulation syndrome (sOHSS) pathogenesis? Are these mutations in the mono- or biallelic state? Design: Two FSHR mutations were found in a pregnant patient affected by sOHSS with no predisposing conditions. While the p.Asn106His mutation is novel, the p.Ser128Tyr mutation has been associated with sOHSS previously. The patient's FSHR gene was analysed by Sanger sequencing, and FSHR cDNAs carrying a single or both point mutations were created by mutagenesis in vitro . cAMP activation by recombinant FSH, luteinizing hormone (LH), human chorionic gonadotropin (HCG) and thyroid-stimulating hormone (TSH) was evaluated in transfected HEK293 cells by bioluminescence resonance energy transfer. Results: All mutations decreased the 50% effective concentration of FSH calculated for cAMP ( P < 0.05, n = 6), resulting in two- to 10-fold lower ligand potency. TSH failed to induce an FSHR-mediated increase in intracellular cAMP, while LH was approximately four-fold more potent than HCG in p.Ser128Tyr FSHR-expressing HEK293 cells despite lower cAMP plateau levels ( P < 0.05, n = 5). The p.Ser128Tyr FSHR mutation was found to be responsible for an LH-/HCG-induced increase in cAMP when it was in the biallelic heterozygous state with p.Asn106His, but no increase in cAMP was induced in the monoallelic state. Conclusion: In-vitro data support that, in pregnant patients with sOHSS, the two FSHR mutations have an opposing effect on the pathogenesis of sOHSS and are in the biallelic heterozygous form, allowing HCG to induce a p.Ser128Tyr FSHR-mediated increase in cAMP.